Нектар любви: роман / Изобель Чейс - Чейс Изобель (Цветы любви, 2003)
Экземпляры: ф.1 (2007) / Инвентарный номер: 51209 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: Ч-36 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44